Future anxiety among special education teachers in light of the Covid-19 pandemic - Altal, Suhair Mamdouh (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to identify the level of future anxiety among special education teachers in light of the Covid 19 pandemic. The descriptive, analytical approach was adopted. The researcher built the future anxiety scale and then verified the indications of its validity and stability. The study sample included (132) teachers of special education in the city of Amman. The results of the study indicated that the level of future anxiety they had was high in all fields and the overall score, whose mean was 3.85, and with regard to the variable of years of experience, the results indicated that there are statistically significant differences. Where the differences were between years of experience (less than 5 years) and (5 years- less than 10 years) in favor of years of experience (5 years- less than 10 years) and between years of experience (less than 5 years) and (10 years and more) In favor of years (10 years or more). As for the gender variable, the results indicated that there are statistically significant differences in the level of future anxiety as a whole, as the results showed that females are more anxious than males, and the study recommended the necessity of holding training workshops for special education teachers seeking to develop their skills and develop their capabilities to face future.